The THE EFFECT OF DEBT TO EQUITY RATIO ON RETURN ON EQUITY IN PT BANK MANDIRI (PERSERO) TBK FOR THE 2014-2018 PERIOD (SURVEY ON THE INDONESIA STOCK EXCHANGE) - Aulia Kusmiawati; Wilma Zuarko Adji; Widwi Handari Adji (JEBS (Journal of Economic and Business Student), 2022)
Kata Kunci : Rasio Utang dengan Modal, Rasio Pengembalian Modal ABSTRACT This research was aimed to determine the influence of debt to equity ratio to the return on equity ratio at PT Bank Mandiri (Persero) Tbk for the 2014-2018 period. The method that used in this research was quantitative methods, data collection techniques is using secondary data by means of documentation, library research and internet research. The data analysis technique used is normality test, correlation coefficient, determination coefficient, simple linear regression analysis and hypothesis testing. As the research has been done, the correlation coefficient is 0,916 this means this had a positive relationship with the level of relationship is very strong. And the determination coefficient was 83,9%. The linear regression equation Y = a + bX = - 25,295 + 6,797 X, that every increase of 1 number debt to equity ratio figure will increase the return on equity ratio by 6,797. The t test result obtained 3,958 > 3,182 (Tcount>Ttable), so Ho is rejected and Ha was accepted which means there was a significant influence between debt to equity ratio and the return on equity ratio. Keyword : Debt to Equity Ratio, Return on Equity